Finnish national election study 1991 - Pesonen, Pertti; Sänkiaho, Risto; Borg, Sami (University of Tampere, 1997)
The 1991 general election in Finland took place on March 17. In connection with the election an election study was carried out, in which respondents were interviewed both before and after the election. The pre-election interview included questions on membership in trade unions, political parties and other organizations. Habits concerning newspapers were also scrutinized, as well as the respondents exposure to news programs on radio and television. Respondents were asked about their general interest in politics, their willingness to join different activities to get influence on certain issues, as well as their participation in different political activities. For a number of statements concerning politics and political parties the respondents had to state if they agreed or disagreed, they had to place seventeen different groups in society on a scale between -50 and +50 depending on if they felt negative or positive towards them, and for a number of power holder in society they had to indicate if they had too much, too little or the right amount of power. Knowledge about current situation in the parliament was tested by questions concerning the four lagerst parties in parliament and parties forming the present government. Furthermore the respondents had to state if they had an intention to vote or not in the coming election, reasons to vote/not to vote and to give an opinion on which issues the political parties should deal with in the election campaign. Respondents intending to vote had to state which party they possibly would vote for, and the reasons why they preferred that party. For all the political parties in parliament the respondents had to give their opinion on the supposed election results. The post-election interview included questions on the election result, interest in the election campaign, general picture of the events prior to the election, and if the respondent believed that the election was influenced by international events such as the Gulf war and the Baltic situation. Respondents were asked about information sources providing support for their voting decision, participation in discussions prior to the election, discussions among family, friends and at work, remembrance of campaign issues and parties presenting them. A number of questions concerned the campaign programs in television, which programs the respondent had viewed and the remembrance of them. Respondents were asked if they had voted in the election and the reason to vote/not to vote. Voters were asked about which party they voted for, main reason for party choice, and on influence on party choice. Furthermore they were asked if they considered party or candidate most important, and reason for candidate choice. Other questions dealt with trust in Finnish politicians, most important political goals, the five most important values in life (Rokeach values), and the respondent´s satisfaction with the financial situation as well as with life over-all. Demographic item include gender, age, occupation, marital status and place of residence.

The 1991 general election in Finland took place on March 17. In connection with the election an election study was carried out, in which respondents were interviewed both before and after the election. The pre-election interview included questions on membership in trade unions, political parties and other organizations. Habits concerning newspapers were also scrutinized, as well as the respondents exposure to news programs on radio and television. Respondents were asked about their general interest in politics, their willingness to join different activities to get influence on certain issues, as well as their participation in different political activities. For a number of statements concerning politics and political parties the respondents had to state if they agreed or disagreed, they had to place seventeen different groups in society on a scale between -50 and +50 depending on if they felt negative or positive towards them, and for a number of power holder in society they had to indicate if they had too much, too little or the right amount of power. Knowledge about current situation in the parliament was tested by questions concerning the four lagerst parties in parliament and parties forming the present government. Furthermore the respondents had to state if they had an intention to vote or not in the coming election, reasons to vote/not to vote and to give an opinion on which issues the political parties should deal with in the election campaign. Respondents intending to vote had to state which party they possibly would vote for, and the reasons why they preferred that party. For all the political parties in parliament the respondents had to give their opinion on the supposed election results. The post-election interview included questions on the election result, interest in the election campaign, general picture of the events prior to the election, and if the respondent believed that the election was influenced by international events such as the Gulf war and the Baltic situation. Respondents were asked about information sources providing support for their voting decision, participation in discussions prior to the election, discussions among family, friends and at work, remembrance of campaign issues and parties presenting them. A number of questions concerned the campaign programs in television, which programs the respondent had viewed and the remembrance of them. Respondents were asked if they had voted in the election and the reason to vote/not to vote. Voters were asked about which party they voted for, main reason for party choice, and on influence on party choice. Furthermore they were asked if they considered party or candidate most important, and reason for candidate choice. Other questions dealt with trust in Finnish politicians, most important political goals, the five most important values in life (Rokeach values), and the respondent´s satisfaction with the financial situation as well as with life over-all. Demographic item include gender, age, occupation, marital status and place of residence.
Finsk valundersökning 1991
Keywords: Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap